2006
DOI: 10.1016/j.asr.2005.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Cluster observations of a magnetic field cavity in the plasma sheet

Abstract: During the recovery phase of a substorm occurring on 1 September 2002 the four Cluster spacecraft crossed from the northern tail lobe into the plasma sheet. While the spacecraft were located in the plasma sheet boundary layer, the magnetic field data from the four spacecraft detected a cavity of close to zero magnetic field. The plasma in this cavity had characteristics similar to that of the central plasma sheet, possibly implying that the central plasma sheet had expanded over and subsequently receded back o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The reduction in lobe flux at the onset of the expansion phase indicated that reconnection either began at, or had already begun by, onset. A little while later, Cluster observed an earthward‐moving diamagnetic cavity embedded within the plasma sheet boundary layer (PSBL), the cause of which remains unclear (Draper et al., 2006). In the second event, the expansion phase onset was observed simultaneously by Cluster, ground magnetometer data and in the injection signature observed by the Polar spacecraft.…”
Section: Nightside Processesmentioning
confidence: 99%
“…The reduction in lobe flux at the onset of the expansion phase indicated that reconnection either began at, or had already begun by, onset. A little while later, Cluster observed an earthward‐moving diamagnetic cavity embedded within the plasma sheet boundary layer (PSBL), the cause of which remains unclear (Draper et al., 2006). In the second event, the expansion phase onset was observed simultaneously by Cluster, ground magnetometer data and in the injection signature observed by the Polar spacecraft.…”
Section: Nightside Processesmentioning
confidence: 99%